2018
DOI: 10.1242/dmm.034116
|View full text |Cite
|
Sign up to set email alerts
|

Cacna1c haploinsufficiency leads to pro-social 50-kHz ultrasonic communication deficits in rats

Abstract: The cross-disorder risk gene CACNA1C is strongly implicated in multiple neuropsychiatric disorders, including autism spectrum disorder (ASD), bipolar disorder (BPD) and schizophrenia (SCZ), with deficits in social functioning being common for all major neuropsychiatric disorders. In the present study, we explored the role of Cacna1c in regulating disorder-relevant behavioral phenotypes, focusing on socio-affective communication after weaning during the critical developmental period of adolescence in rats. To t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

17
124
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(143 citation statements)
references
References 48 publications
17
124
2
Order By: Relevance
“…55 Acoustic communication is another prominent element of the rat social behavior repertoire. 45 Despite no alterations in rough-andtumble play behavior, 50-kHz USV were consistently reduced across all play sessions in male Cacna1c haploinsufficient rats, possibly reflecting reduced liking 69 of playful interactions. [56][57][58] Converging evidence from selective breeding, surgical devocalization, and sound playback studies supports the notion that such USV serve as situation-dependent socio-affective signals, with specific USV types fulfilling distinct communicative functions.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…55 Acoustic communication is another prominent element of the rat social behavior repertoire. 45 Despite no alterations in rough-andtumble play behavior, 50-kHz USV were consistently reduced across all play sessions in male Cacna1c haploinsufficient rats, possibly reflecting reduced liking 69 of playful interactions. [56][57][58] Converging evidence from selective breeding, surgical devocalization, and sound playback studies supports the notion that such USV serve as situation-dependent socio-affective signals, with specific USV types fulfilling distinct communicative functions.…”
mentioning
confidence: 85%
“…45 Despite no alterations in rough-andtumble play behavior, 50-kHz USV were consistently reduced across all play sessions in male Cacna1c haploinsufficient rats, possibly reflecting reduced liking 69 of playful interactions. 80 In fact, in our recent study in male Cacna1c haploinsufficient rats, 45 we found that a decrease in Ca v 1.2 expression levels not only leads to impairments in ultrasonic communication in the sender but also in the recipient rat. [72][73][74] As repeatedly demonstrated in playback studies, 50-kHz USV serve important pro-social communicative functions.…”
mentioning
confidence: 85%
See 3 more Smart Citations